Optical smart packaging to reduce transmitted information - Cabezas Burbano, Luisa Fernanda (2012)
We demonstrate a smart image-packaging optical technique that uses what we believe is a new concept to save byte space when transmitting data. The technique supports a large set of images mapped into modulated speckle patterns. Then, they are multiplexed into a single package. This operation results in a substantial decreasing of the final amount of bytes of the package with respect to the amount resulting from the addition of the images without using the method. Besides, there are no requirements on the type of images to be processed. We present results that proof the potentiality of the technique.